Associations between childhood and adulthood socioeconomic position and grip strength at age 46 years: findings from the 1970 British Cohort Study - Mohamed Yusuf; Gallin Montgomery; Mark Hamer; Jamie McPhee; Rachel Cooper (BMC, 2022)
Abstract Background Muscle weakness is a key criterion for important age-related conditions, including sarcopenia and frailty. Research suggests lower childhood socioeconomic position (SEP) may be associated with muscle weakness in later life but there is little evidence on associations in younger adults closer to peak muscle strength. We aimed to examine relationships between indicators of SEP in childhood and adulthood and grip strength at age 46y. Methods We examined 7,617 participants from the 1970 British Cohort Study with grip strength measurements at 46y. We used sex-specific linear regression models to test associations between five different indicators of SEP in childhood and adulthood (paternal occupational class and parental education levels at age 5 and own occupational class and education level at age 46) and maximum grip strength. Models were adjusted for birth weight, BMI in childhood and adulthood, adult height, disability in childhood, leisure-time physical activity in childhood and adulthood, sedentary behaviour in childhood and adulthood, occupational activity and smoking at age 46. Results Among women, lower SEP in childhood and adulthood was associated with weaker grip strength even after adjustments for covariates. For example, in fully-adjusted models, women whose mothers had no qualifications at age five had mean grip strength 0.99 kg (95% CI: -1.65, -0.33) lower than women whose mothers were educated to degree and higher. Among men, lower levels of father's education and both adult SEP indicators were associated with stronger grip. The association between own occupational class and grip strength deviated from linearity; men in skilled-manual occupations (i.e. the middle occupational group) had stronger grip than men in the highest occupational group (Difference in means: 1.33 kg (0.60, 2.06)) whereas there was no difference in grip strength between the highest and lowest occupational groups. Adjustment for occupational activity largely attenuated these associations. Conclusion Findings highlight the need to identify age and sex-specific interventions across life to tackle inequalities in important age-related conditions related to weakness.